2012
DOI: 10.1016/j.spmi.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A new large – Scale synthesis of magnesium oxide nanowires: Structural and antibacterial properties

Abstract: Highlights► Low temperature microwave hydrothermal method is developed to synthesize MgO nanowires. ► The antibacterial properties of MgO nanowires have been examined. ► This novel method serve a direct route for mass production of MgO nanowires and antibacterial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(70 citation statements)
references
References 22 publications
1
69
0
Order By: Relevance
“…It was observed that the values of calculated cell parameters ( and ) were slightly greater than that of bulk CuAlO 2 ( = 0.2856 nm and = 1.6943 nm). This phenomenon could occur due to the influence of lattice expansion caused by the increase in oxygen vacancy and Al 3 ions with reduced particle size and increased surface relaxation during the grain growth process [4,12]. Figure 2 displays EDS spectra of CuAlO 2 nanowires.…”
Section: Morphologies and Structures Of Delafossite Cualo 2 Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the values of calculated cell parameters ( and ) were slightly greater than that of bulk CuAlO 2 ( = 0.2856 nm and = 1.6943 nm). This phenomenon could occur due to the influence of lattice expansion caused by the increase in oxygen vacancy and Al 3 ions with reduced particle size and increased surface relaxation during the grain growth process [4,12]. Figure 2 displays EDS spectra of CuAlO 2 nanowires.…”
Section: Morphologies and Structures Of Delafossite Cualo 2 Nanowiresmentioning
confidence: 99%
“…Generally, nanofluids possess some remarkable properties, such as less clogging problem, reduced heat transfer system size, higher thermal conductivity, better stability, and lower pressure [10,11]. In recent years, different scientific endeavors have been carried out in the quest of new nanofluid composites with improved parameters [12]. Nanofluids can be synthesized by either one-or two-step methods.…”
Section: Introductionmentioning
confidence: 99%
“…21 It has been reported that GO-silver (Ag) shows excellent antibacterial properties against many bacterial species. 22,23 Metal nanoparticles have generated wide interest and focus, and are used in diverse field of research, most importantly, in biological and medical areas, 24 such as titanium dioxide, 25 zinc oxide, 26 magnesium, 27 gold, 28 copper 29 and Ag. 30 Ag, a nonspecific biocidal agent, is of particular interest due to its significant antimicrobial activity against a broad spectrum of fungus, viruses and bacteria, even antibioticresistant strains.…”
Section: Introductionmentioning
confidence: 99%
“…MgO nanoparticles are of specific interest as they exhibit excellent biocompatibility. MgO nanoparticles are used in various applications like photo catalysis, as bactericidal, for waste remediation and drug delivery [5][6][7]. In materials science and technology, the structure -property relationship dictates the functional attributes of the materials which also depend upon the synthesis routes for these materials.…”
Section: Introductionmentioning
confidence: 99%